Impact of the COVID-19 Pandemic on Infectious Diseases in Brazil: A Case Study on Dengue Infections - Federico Borre; Juliette Ildiko Borri; Yuval Zoy Cohen; Mariana Gasparoto; Tsewang Bhumchok Gurung (MDPI AG, 2022)
Brazil is known for being a breeding ground for emerging infectious diseases (EIDs), such as Zika, dengue, and chikungunya. Given that it has been one of the countries most affected by the SARS-CoV-2 pandemic, this article aims to analyze the impact that the COVID-19 pandemic has had on the burden of infectious diseases in Brazil, especially that of dengue. Brazil is a unique territory with a heterogeneous population living in a tropical, wet climate favorable to infectious diseases. In addition, despite being one of the largest emerging economies in the world, the country has been exposed to political instability and a public health system that suffers from large funding shortfalls and a lack of coherent regulation. The findings from this study are multilayered. Firstly, as cases of COVID-19 rose at the start of the pandemic, cases of dengue declined drastically. This may be due, in part, to factors such as seasonal climate and distancing measures. Furthermore, the findings indicate that the diversion of resources away from dengue and other infectious diseases, and mobilization for COVID-19 testing and treatment, likely resulted in a serious underreporting of dengue. While Brazil has incorporated some of the lessons learned from past EID experience in responding to the COVID-19 pandemic, the analysis highlights how the country's structural problems present pitfalls in the epidemiological fight. It was concluded that in a country such as Brazil, where infectious disease outbreaks are only a matter of time, pandemic preparedness should be prioritized over pandemic response.